2018
DOI: 10.18805/ijar.b-3588
|View full text |Cite
|
Sign up to set email alerts
|

Detection and isolation of Duck Plague virus from field outbreaks in Assam, India

Abstract: Duck plague is an acute, contagious and lethal disease of ducks caused by an enveloped DNA virus, belonging to Anatid Herpes Virus 1 under genus Mardivirus, subfamily Alphaherpesvirinae, family Herpesviridae. The disease is characterized by sudden death, high mortality, hemorrhages and necrosis in the internal organs. Duck farming plays an important role in the livelihood of the farmers of Assam. Duck Plague being the major killer disease among duck population of Assam, posing a threat to the growth of duck fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The DNA polymerase gene encodes UL30 protein, which is highly conserved in DPV ( Wallace et al ., 2000 ; OIE, 2012 ; Wu et al ., 2012 ; Ahamed et al ., 2015 ). UL30 is involved in DNA replication and nucleotide metabolism in DPV ( Li et al ., 2006 ; Neher et al ., 2019 ). It is widely used to construct phylogenetic trees and to indicate a distinct division among Alphaherpesvirinae, Betaherpesvirinae, and Gammaherpesvirinae ( Thureen and Keeler, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…The DNA polymerase gene encodes UL30 protein, which is highly conserved in DPV ( Wallace et al ., 2000 ; OIE, 2012 ; Wu et al ., 2012 ; Ahamed et al ., 2015 ). UL30 is involved in DNA replication and nucleotide metabolism in DPV ( Li et al ., 2006 ; Neher et al ., 2019 ). It is widely used to construct phylogenetic trees and to indicate a distinct division among Alphaherpesvirinae, Betaherpesvirinae, and Gammaherpesvirinae ( Thureen and Keeler, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…It targeted Ducks showing typical clinical signs of DP including the in contact Healthy ducks and the dead birds suspected to be dead of DPV infection to collect different clinical and postmortem samples for the study. Post Mortem (PM) examination was conducted according to (Neher et al, 2019, El-Tholoth et al, 2019 for dead and live infected birds and it scrutinized all internal organs for presence of typical DP lesions. During the PM review, visceral organs like the heart, esophagus, proventriculus, spleen, liver and intestine were collected.…”
Section: Methods Of Sample Collectionmentioning
confidence: 99%
“…In 1923 the first known occurrence of DVE was recorded in the Netherlands (Mondal et al, 2010, Baudet, 1923.The first DP Virus (DPV) isolation and identification study was published in Bangladesh in 1982, subsequently evaluating the immunogenicity of the DPV vaccine from local isolates (Wu et al, 2012a, Ahamed et al, 2015a, Hossain et al, 2005a, Islam et al, 2005. The morbidity and mortality rates of suspected birds vary between 5% and 100%, depending on the virulence of bird infection and immunological status (Neher et al, 2019) that causes acute hemorrhagic, septic, infectious, and fatal diseases among waterfowls such as ducks, geese, and swans, (Li et al, 2009, You et al, 2018, El-Tholoth et al, 2019, Wu et al, 2012a, which caused major economic losses in the commercial waterfowl industry around the world as a result of sudden deaths, condemnations, and reduced production of eggs (Cai et al, 2010, Lian et al, 2010. Natural infections of waterfowls are susceptible at all ages and there reported that in young ducks from 7 days of age (El-Samadony et al, 2013, El-Tholoth et al, 2019) and infected with direct or indirect contact and developed clinical manifestation within 3 to 7 days after infection (Wang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In India, the disease outbreak was recorded in West Bengal 4 , Karnataka 5 , UĴ ar Pradesh 6 , Kerala 7 , Tamil Nadu [8][9] and Assam 10 . More than 25 outbreaks were recorded in various districts of Assam state in India during the period from August 2012 to December 2015 11 . The present study reports the occurrence of duck viral enteritis outbreak in the Cauvery delta region of Tamil Nadu.…”
mentioning
confidence: 99%